2020
DOI: 10.1021/acs.jctc.0c00101
|View full text |Cite
|
Sign up to set email alerts
|

Excitons in Solids from Periodic Equation-of-Motion Coupled-Cluster Theory

Abstract: We present an ab initio study of electronically excited states of three-dimensional solids using Gaussian-based periodic equation-of-motion coupled-cluster theory with single and double excitations (EOM-CCSD). The explicit use of translational symmetry, as implemented via Brillouin zone sampling and momentum conservation, is responsible for a large reduction in cost. Our largest system studied, which samples the Brillouin zone using 64 k-points (a 4 × 4 × 4 mesh) corresponds to a canonical EOM-CCSD calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 152 publications
5
68
0
Order By: Relevance
“…CC has been successfully used for excited state calculations [28][29][30]. Wang and Berkelback [31] have recently shown that Equation-of-Motion Coupled-Cluster Theory can yield promising results for optical excitation energies, exciton binding energies, exciton dispersion relations, and exciton-phonon interaction energies of simple crystalline solids like Si, C, SiC, MgO, or LiF. Other attempts are made in this direction for ground-state and excited-state methods that combine CC and perturbation theory based on a partitioning of excitations that are internal or external to an active space [32][33][34][35].…”
Section: Coupled Cluster Theorymentioning
confidence: 99%
“…CC has been successfully used for excited state calculations [28][29][30]. Wang and Berkelback [31] have recently shown that Equation-of-Motion Coupled-Cluster Theory can yield promising results for optical excitation energies, exciton binding energies, exciton dispersion relations, and exciton-phonon interaction energies of simple crystalline solids like Si, C, SiC, MgO, or LiF. Other attempts are made in this direction for ground-state and excited-state methods that combine CC and perturbation theory based on a partitioning of excitations that are internal or external to an active space [32][33][34][35].…”
Section: Coupled Cluster Theorymentioning
confidence: 99%
“…In a similar spirit, one could perform a HF calculation in a large Gaussian basis and then perform an MP2 calculation with some number of frozen virtual orbitals. 10,84 Similar corrections are impossible with the original GTH basis set series due to the high linear dependencies at the QZ (or even TZ) level [Fig. 1(a)].…”
Section: Convergence To the Full Virtual Space Limit: Mp2 Ground-stat...mentioning
confidence: 99%
“…Recent years have witnessed a rapid growth of interest in understanding condensed-phase materials using quantum chemistry methods, [1][2][3][4][5][6][7][8][9][10][11][12][13] especially those beyond density functional theory 14,15 (DFT) with local and semi-local exchange-correlation functionals. 16,17 The non-local exchange and the many-body electron correlation in the quantum chemistry methods promise many advantages, such as systematic improvability 7 and the ability to describe dispersion interactions [18][19][20] and strong electron correlations, 21,22 but are also computationally demanding, especially when using a plane-wave (PW) basis set due to the slow convergence with the number of virtual bands.…”
Section: Introductionmentioning
confidence: 99%
“…The equation-of-motion (EOM) formalism is one way to obtain excited state properties from a coupled cluster ground state [50][51][52] . Though most commonly used for molecular electronic excited states, EOM-CC methods have been applied to excitations in periodic solids 36,[53][54][55] as well as to vibrational excited states in molecules 40,44,47,56 . In this work we describe a coupled cluster theory and corresponding EOM extension for interacting electrons and phonons.…”
Section: Introductionmentioning
confidence: 99%